MANAJEMEN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DAN BANTUAN OPERASIONAL SEKOLAH DAERAH (BOSDA) DI SMP NEGERI 11 YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Management of School Operational Assistance (BOS) and Regional School Operational Assistance (BOSDA) Fund was a part of school management system which had a purpose to create accountable and reliable expenditure. Schools was responsibled to manage the expenditure as effect of the regulation of school based management.This research was done at State Junior High School 11 Yogyakarta, the research subjects were : headmaster, vice of headmaster, school treasurer, teacher, employee, school committee, students, and students parents. Data collection was done by observation, interview, and documentation methods. Data analysis was done by qualitative descriptive method measuring the facts, characteristics, and relationships among observed phenomenons. The steps were data reduction, data display, and making conclusions. The research outcome shows that, the management of BOS and BOSDA fund is done through arrangement series of : (1) budgeting involves planning fund resource management, setting program priority, estimating fund sufficiency, and compiling School Budgeting Planning, (2) accounting involves accepting, withdrawing, and expending fund, expenditure after-tax, and administration, and (3) auditing involves monitoring and supervision, controlling, inspecting, and punishment. Factors supporting the management of BOS and BOSDA fund are : participative School Budgeting Planning, credible BOS management team at the school level, continual controlling by headmaster, and the absence of deviation. Factors Obstructing the management of BOS and BOSDA fund are: school component do not understand the use of fund and its prohibition, late fund liquidation, unpredictable spending, increase in goods or service price, and inspection without information. The goverment is advised to make more effective socialization ofBOS and BOSDA program, and be flexible to apply the regulation so that the school will be more creative in developing program.